MANAJEMEN SARANA PRASARANA PENDIDIKAN ANAK USIA DINI DI TK PELANGI ANAK NEGRI YOGYAKARTA - Ucik Hidayah Binsa (Jurnal CARE (Children Advisory Research and Education), 2021)
Abstract Management of infrastructure and infrastructure in accordance with the minimum regulations of the Ministry of Education and Culture is one of the important factors to support and the success of the learning process, the method used in this study is descriptive with a qualitative approach. This study aims to describe how the management of infrastructure facilities and how infrastructure in Pelangi Anak Negri Yogyakarta Kindergarten. These processes include planning infrastructure, procuring infrastructure, inventorying infrastructure, maintaining and responsible for infrastructure, eliminating infrastructure that can no longer be used.Abstrak Manajemen sarana prasarana dan sarana prasarana yang sesuai ketentuan minimal permendikbud merupakan salah satu faktor penting untuk menunjang dan keberhasilan proses berjalannya pembelajaran, metode yang digunakan dalam penelitian ini adalah deskriptif dengan pendekatan kualitatif. Penelitian ini bertujuan untuk mendeskripsikan bagaimana manajemen sarana prasarana dan bagaimana sarana prasarana di TK Pelangi Anak Negri Yogyakarta. Proses tersebut antar lain adalah perencanaan sarana prasarana, pengadaan sarana prasarana, penginventarisan sarana prasarana, perawatan serta penanggungjawab sarana prasarana, penghapusan sarana prasarana yang sudah tidak bisa dipakai.